Pengaruh Stres Kerja, Beban Kerja, dan Spiritualitas terhadap Kinerja Penyelenggara Pemilu (Badan Ad-Hoc) di Komisi Pemilihan Umum (KPU) DKI Jakarta - Alwi, Suhaimi; Mulyono, Rachmat (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study examines the impact of work stress, workload, and spirituality on the performance of election officers in the Ad-Hoc bodies of the General Election Commission (KPU) in DKI Jakarta. The research explores how work stress and excessive workloads negatively affect performance and well-being, while workplace spirituality plays a significant role in improving performance. A quantitative approach was used, with a survey conducted among the District Election Committee (PPK) and the Voting Committee (PPS). The findings reveal that high work stress and heavy workloads lead to reduced productivity, increased errors, and mental fatigue. In contrast, a strong sense of spirituality enhances ethical awareness, resilience, and intrinsic motivation, thereby improving overall performance. This study recommends policies to manage work stress, better distribute workloads, and integrate spirituality into the workplace to support election officers' well-being and effectiveness.